2021
DOI: 10.2355/isijinternational.isijint-2020-743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooling Rate after Hot Forging on Precipitation of Fine Particles during Subsequent Normalizing and Austenite Grain Growth during Carburization of Al- and Nb-microalloyed Case-hardening Steel

Abstract: This study deals with austenite grain growth during high-temperature carburization of an Al-and Nb-microalloyed case-hardening steel. The grain size after carburization-simulated heating for 5 h at 1 050°C decreased with the increase in the cooling rate from hot forging-simulated heating for 1 h at 1 250°C. The increase in cooling rate led to the decreases in the volume fractions and sizes of AlN and Nb(C,N) particles precipitated during cooling, and AlN disappeared when the cooling rate increased to 16°C/min,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…4, some of AlN particles were combined with Nb(C, N) particles. AlN (1120) plane is well matched with the Nb(C, N) (220) plane, and the AlN-Nb(C, N) interface has high coherence, according to our recent study 18) . Therefore, it was considered that AlN precipitated on Nb(C, N) with a low interfacial energy.…”
Section: Precipitation Behavior Of Aln During Normalizingsupporting
confidence: 67%
See 3 more Smart Citations
“…4, some of AlN particles were combined with Nb(C, N) particles. AlN (1120) plane is well matched with the Nb(C, N) (220) plane, and the AlN-Nb(C, N) interface has high coherence, according to our recent study 18) . Therefore, it was considered that AlN precipitated on Nb(C, N) with a low interfacial energy.…”
Section: Precipitation Behavior Of Aln During Normalizingsupporting
confidence: 67%
“…In our previous study, we focused on an Al-and Nb-microalloyed case-hardening steel and found that forging-simulated heating at 1250 °C for 1 h completely dissolved AlN and Nb(C, N) 17) , and we also found the effects of the cooling rate after the forging-simulated heating on the precipitation behaviors of particles, as follows 18) . When cooled at 16 °C/min, a small number of Nb(C, N) particles precipitated during cooling, whereas the AlN particles did not precipitate.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the precipitation mechanism and sequence for AlN-Nb(C,N) remain unclear. Saito [32] reported that the Nb(C,N) precipitates served as the role of nucleation sites for AlN due to a coherent AlN-Nb(C,N) interface, but Leap [33] claimed Nb(C,N) precipitation occurred heterogeneously on preexisting AlN precipitates. It is worthwhile to further investigate the synergistic effect of Al-Nb microalloying on precipitation behaviors and austenite grain growth.…”
Section: Introductionmentioning
confidence: 99%